Parvulin 14 and Parvulin 17 Bind to HBx and cccDNA and Upregulate Hepatitis B Virus Replication from cccDNA to Virion in an HBx-Dependent Manner - Saeed, Umar (J Virol, 2019)
The parvulin 14 (Par14) and parvulin 17 (Par17) proteins, which are both encoded by the PIN4 gene, play roles in protein folding, chromatin remodeling, DNA binding, ribosome biogenesis, and cell cycle progression. However, the effects of Par14 and Par17 on viral replication have never been explored. In this study, we found that, in the presence of HBx, either Par14 or Par17 could upregulate hepatitis B virus (HBV) replication, whereas in the absence of HBx, neither Par14 nor Par17 had any effect on replication. Overexpression of Par14/Par17 markedly increased the formation of covalently closed circular DNA (cccDNA), synthesis of HBV RNA and DNA, and virion secretion. Conversely, PIN4 knockdown significantly decreased HBV replication in HBV-transfected and -infected cells. Coimmunoprecipitation revealed that Par14/Par17 engaged in direct physical interactions with HBx in the cytoplasm, nucleus, and mitochondria, possibly mediated through substrate-binding residues on Par14/Par17 (E46/D74 and E71/D99, respectively) and conserved (19)R(20)P-(28)R(29)P motifs on HBx. Furthermore, these interactions enhanced HBx stability, promoted HBx translocation to the nuclear and mitochondrial fractions, and increased HBV replication. Chromatin immunoprecipitation assays revealed that, in the presence of HBx, Par14/Par17 were efficiently recruited to cccDNA and promoted transcriptional activation via specific DNA-binding residues (S19/44). In contrast, in the absence of HBx, Par14/Par17 bound cccDNA only at the basal level and did not promote transcriptional activation. Taken together, our results demonstrate that Par14 and Par17 upregulate HBV RNA transcription and DNA synthesis, thereby increasing the HBV cccDNA level, through formation of the cccDNA-Par14/17-HBx complex. IMPORTANCE The HBx protein plays an essential regulatory role in HBV replication. We found that substrate-binding residues on the human parvulin peptidylprolyl cis/trans isomerase proteins Par14 and Par17 bound to conserved arginine-proline (RP) motifs on HBx in the cytoplasm, nucleus, and mitochondria. The HBx-Par14/Par17 interaction stabilized HBx; promoted its translocation to the nucleus and mitochondria; and stimulated multiple steps of HBV replication, including cccDNA formation, HBV RNA and DNA synthesis, and virion secretion. In addition, in the presence of HBx, the Par14 and Par17 proteins bound to cccDNA and promoted its transcriptional activation. Our results suggest that inhibition or knockdown of Par14 and Par17 may represent a novel therapeutic option against HBV infection.